Multi-objective sustainable capacitated location routing problem formulation in sustainable supply-chain management. Issue 3 (4th March 2023) - Galindres, Luis Fernando; Guimarães, Frederico Gadelha; Gallego-Rendón, Ramón Alfonso
Abstract : Conflicting sustainability dimensions are considered in a multi-objective formulation, focusing on the capacitated location routing problem (CLRP). The proposed sustainable version (S-CLRP) addresses the location of facilities, the routing of vehicles, the balance of the working load among drivers, and the environmental impact of operations due to the emission of greenhouse gases. In this work, both a mixed integer linear programming model solved using the goal attainment method and an approximated method based on iterated local search (ILS) and decomposition (ILS/D) are proposed. The results show the generation of non-dominated fronts with adequate dispersion and convergence characteristics with which supply-chain decision-makers can evaluate the impact of their decisions on the financial, environmental and social dimensions of their operations.